1973
DOI: 10.1029/jc078i021p04489
|View full text |Cite
|
Sign up to set email alerts
|

Slowly varying stokes waves and submarine longshore bars

Abstract: We investigate the mass transport velocity in the Stokes boundary layer due to slowly varying Stokes waves impinging on and reflecting from a plane‐sloping beach. The resulting mass transport velocity distribution is interpreted to indicate the possible locations of submarine longshore sandbar formation. It is found that the number of bars is likely to increase when the bottom gradient is slight and that the spacing between the crests of the bars increases seaward for some distance offshore. These results are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
30
1

Year Published

1975
1975
2012
2012

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(32 citation statements)
references
References 10 publications
(4 reference statements)
1
30
1
Order By: Relevance
“…This does not agree with the findings of earlier investigators, (Zenkovich 1967, Lau andTravis 1973). The size of the sample in our study, 504 profiles, and the geographic distribution, from Long Island to Texas, were sufficient to adequately establish such a relationship if it did exist.…”
contrasting
confidence: 55%
See 4 more Smart Citations
“…This does not agree with the findings of earlier investigators, (Zenkovich 1967, Lau andTravis 1973). The size of the sample in our study, 504 profiles, and the geographic distribution, from Long Island to Texas, were sufficient to adequately establish such a relationship if it did exist.…”
contrasting
confidence: 55%
“…However when there are bars under these conditions, they occur in the forward portion and at the seaward end of the profile. Lau and Travis (1973) found that "the number of bars is likely to increase when the bottom gradient is slight;" Zenkovich (1967) noted that the formation of bars was restricted to a fairly narrow range of slopes (0.02-0.005). In our eigenvector analyses of the 504 profiles of the basic data set, we found that the attribute of profile slope is independent of profile curvature elements; that is, bars.…”
Section: Profiles Without Barsmentioning
confidence: 99%
See 3 more Smart Citations